Properties of biobased epoxy resins from epoxidized linseed oil (ELO) crosslinked with a mixture of cyclic anhydride and maleinized linseed oil - M. D. Samper; J. M. Ferri; A. Carbonell-Verdu; R. Balart; O. Fenollar (eXPRESS Polymer Letters, 2019)
This works aims at the development thermosetting resins derived from epoxidized linseed oil (ELO) of high biobased content, by using a mixture of crosslinking agents, i.e. methyl nadic anhydride (MNA) and maleinized linseed oil (MLO). By using only MNA as crosslinking agent, the obtained resins are characterized by high stiffness and, consequently, high fragility. When MLO content increasing in the crosslinking mixture, up to 25 wt%, a decrease in mechanical resistant and thermomechanical is detected, thus indicating that MLO can provide flexibility to ELO-based thermosetting resins which is an interesting issue to obtain tailored properties by selecting the appropriate mixture composition. In general, the thermosetting resin crosslinked with 10 wt% MLO and 40 wt% MNA gives balanced properties together with noticeable biobased content, thus broadening the potential of these materials for uses in green composites and coatings.